Experiencia profesional en el área de desarrollo de software - Momediano Almonacid, Moritz (2022)
As a professional graduated from the University of Lima, I had the opportunity to face different challenges in different work areas, I started in the area of networks and communications, supporting the creation of network topologies and the configuration of communication devices, then in the area of help desk, providing support to the Windows 10 operating system and finally in the area of development and innovation, where I faced all the new challenges thanks to my knowledge acquired in the systems engineering career at the university and self-taught learning about new technologies for software development. This last experience allowed me to make a choice about my career as a software developer, with which I can provide technological and innovative solutions, as well as participate in the design, development and implementation of a web or mobile application. Having enough technical experience in software development, such as automating tasks, improving workflows, adding new functionalities to the systems used by the different interested clients, among others, allowed me to be a project manager as a technical leader. This previous experience allowed me to participate in decision-making with different teams, to achieve their objectives, according to the need and the goals set. In this report I detail my work experience, in which I highlight my role as a developer, especially my participation in the analysis and development of technological solutions in the different projects in which I participated.